Anatomical breast imaging-derived parameters do not provide incremental information in prediction of nonvisualization of sentinel lymph nodes on lymphoscintigraphy. Issue 8 (18th May 2022) - Chahid, Youssef; Verberne, Hein J.; Poel, Edwin; Hendrikse, N. Harry; Booij, Jan
Abstract : Objective: Accurate sentinel lymph node (SLN) staging is essential for both prognosis and treatment in patients with breast cancer. However, the preoperative lymphoscintigraphy may fail to visualize the SLN. The aim of this retrospective study was to investigate whether parameters derived from anatomical breast imaging can predict SLN nonvisualization on lymphoscintigraphy. Methods: For this retrospective study, all data of mammography, breast MRI, and lymphoscintigraphy of SLN procedures from January 2016 to April 2021 were collected and reviewed from the Amsterdam UMC database. Results: A total of 758 breast cancer patients were included in this study. SLN nonvisualization on planar lymphoscintigraphy at 2-h postinjection (pi) was 29.7% and was reduced after a second injection to 7.5% at late lymphoscintigraphy 4-h pi. Multivariable analysis showed that age ≥ 70 years ( P = 0.019; OR, 1.82; 95% CI, 1.10–3.01), BMI ≥ 30 kg/m 2 ( P = 0.031; OR, 1.59; 95% CI, 1.04–2.43), and nonpalpable tumors ( P = 0.034; OR, 1.54; 95% CI, 1.03–2.04) were independent predictors of SLN nonvisualization. Differences in tumor size, Breast Imaging-Reporting and Data System classification, or breast density were not significantly associated with SLN nonvisualization. Conclusion: This study shows that, by using a multivariable analysis, risk factors for SLN nonvisualization in breast cancer patients during preoperative lymphoscintigraphy at 2-h pi are age ≥ 70 years, BMI ≥ 30 kg/m 2, and nonpalpable tumors. Parameters derived from mammography or breast MRI, however, are not useful to predict SLN nonvisualization on lymphoscintigraphy.